New observations of the endangered giant freshwater whipray, Urogymnus polylepis, provide further evidence for its distribution and breeding in the north‐east coast of India. Issue 6 (11th October 2022) - Sen, Swatipriyanka; Thomas, Sujitha; Joe Kizhakudan, Shoba; Dash, Gyanaranjan; Pradhan, Rajesh Kumar; Ghosh, Shubhadeep; Das, Madhumita; Dash, Biswajit; Zacharia, Pariyappanal Ulahannan
Abstract: The present study reports observations of 13 giant freshwater whipray ( Urogymnus polylepis ) from commercial fish landings along the north‐east coast of India and updates existing records based on field observations and local social media reports. The disc width of the landed specimens ranged from 120 to 223 cm and they weighed 95–300 kg. All 13 specimens observed were mature (nine females and four males) and three females were pregnant, with embryo numbers ranging between 4 and 15. Globally, U. polylepis is listed as 'Endangered', and greater protection measures are needed in India to assist in reversing current population declines.